Muhammad Shalih As-Samarani (1820-1903 M): Representasi Dakwah Islam Nusantara dalam Kajian Akademis - Miftahuddin Khairi; Aflahal Misbah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The aim of this paper is to understand how the da’wa of Islam Nusantara by Muhammad Shalih as-Samarani is represented in academic works. Data of this paper are 18 academic manuscripts dated from 2015 to date. This paper finds that there are two strands of representations about the Islam Nusantara of Muhammad Shalih as-Samarani; the dominant narrative and the ‘other alternative’. Both narratives present as-Samarani as different actor. The first narrative present as-Samarani as a mufassir (interpreter of the Qur’an) and the second narrative present as-Samarani as a person who has deep knowledge on multiple disciplines such as fiqh, orthodox tasawwuf, and education. However, both narratives share one thing in common; they present as-Samarani as a Sufi Muslim who contributed greatly to the dialogue between Islamic teachings and elements of local wisdoms.Keywords: academic works, as- Samarani, and representation of Islam Nusantara.